2011
DOI: 10.2174/157488411794941331
|View full text |Cite
|
Sign up to set email alerts
|

Bronchodilator Combination Therapy for the Treatment of Chronic Obstructive Pulmonary Disease

Abstract: Chronic obstructive pulmonary disease (COPD) is a major cause of morbidity and mortality, and its prevalence is rising worldwide. Bronchodilators remain the cornerstone of COPD treatment, especially inhaled β2-adrenergic receptor agonists and inhaled anticholinergics. Long-acting bronchodilators are considered more effective and convenient than short-acting bronchodilators for the maintenance treatment in patients with moderate to very severe COPD. There are currently 3 long-acting inhaled bronchodilators avai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…The combination is only second-line therapy in GOLD 2011, but it is an important combination. Studies with COPD patients combining a LAMA and a LABA have demonstrated greater improvements in lung function (specifically FEV 1 ) than either bronchodilator alone [51]. β 2 -adrenergic receptor agonists bind to β 2 adrenoreceptors on the surface of smooth muscle cells at all levels of the airways (even in the small airways involved in COPD), leading directly to relaxation of smooth muscle and subsequent bronchodilation [52, 53].…”
Section: Pharmacotherapy Of Copdmentioning
confidence: 99%
“…The combination is only second-line therapy in GOLD 2011, but it is an important combination. Studies with COPD patients combining a LAMA and a LABA have demonstrated greater improvements in lung function (specifically FEV 1 ) than either bronchodilator alone [51]. β 2 -adrenergic receptor agonists bind to β 2 adrenoreceptors on the surface of smooth muscle cells at all levels of the airways (even in the small airways involved in COPD), leading directly to relaxation of smooth muscle and subsequent bronchodilation [52, 53].…”
Section: Pharmacotherapy Of Copdmentioning
confidence: 99%
“…9,10 Additional factors, including patient adherence and inhaler technique, also contribute to treatment outcomes. 11 Long-acting bronchodilator therapy is the cornerstone treatment for most patients with COPD; 4,12 for some patients with mild disease, and low symptom burden, short-acting bronchodilators may suffice for symptom control, 4 but in many cases they should be used only as rescue medications. Inhaled long-acting β2-agonists (LABAs) and long-acting anticholinergic (or antimuscarinic) bronchodilators (LAMAs) are regularly used for maintenance treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Inhaled long-acting β2-agonists (LABAs) and long-acting anticholinergic (or antimuscarinic) bronchodilators (LAMAs) are regularly used for maintenance treatment. 5,12 Combining bronchodilators of different pharmacological classes may improve efficacy and decrease the risk of side effects compared with higher doses of monocomponents. 13 Four fixed-dose LAMA/LABA combinations are now available in the US in a single delivery device; however, it may be unclear which patients would benefit more from dual rather than single bronchodilator therapy as initial treatment, and which inhaler device would be most appropriate for each patient.…”
Section: Introductionmentioning
confidence: 99%
“…1 Combining bronchodilators of different classes leads to an improvement in efficacy with fewer adverse events in comparison with increased doses of the monocomponents. 15 …”
Section: Introductionmentioning
confidence: 99%